Unsur Pembangun Naskah Drama Sudah Gila Karya Chairil Anwar - Iktarna Faris Saufaqillah; Akhmad Fatoni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to analyze the structure of the drama script by Chairil Anwar entitled " Sudah Gila" using a structural approach. The method applied in this study is a qualitative descriptive approach with a focus on library research. Data collection techniques include reading techniques, inventory techniques, and recording techniques. Through reading all the data obtained will be grouped based on the object of research. After being grouped, the data will be described according to the existing conditions and arranged into a report. The results of the study, the conflict that occurs in the script, namely a man who is upset over the death of his beloved wife, and is upset why good people are taken first by God, why not bad people. This is a conflict or central problem in the drama script " Sudah Gila" by Chairil Anwar. The plot in this script is a forward plot. The setting in this drama script is in the Village, Teras Rumah. Conclusion, based on the analysis that the author did on the drama script, it is a type of imaginative drama as well as possibly a tragedy drama, because the climax of the story is about sadness and confusion.